Exploration of self-regulated learning among kampus merdeka internship participants in terms of environmental factor: Eksplorasi self-regulated learning pada mahasiswa peserta program magang kampus merdeka ditinjau dari faktor lingkungan (Psikologia: Jurnal Pemikiran dan Penelitian Psikologi, 2022)
Self-Regulated Learning (SRL) is an individual's active participation in the learning process (Zimmerman, 1990). This study aims to examine the differences in SRL of Kampus Merdeka Internship Participants in terms of environmental factors, including the Internship System (WFO, WFH, and Hybrid), Internship Duration (10 hours), and Attendance Model (Attending Lectures and Not Following Lectures). The results showed that there was no difference in the SRL of the Kampus Merdeka Internship participants to the Internship System and Internship Duration. However, there is a difference in SRL for the Kampus Merdeka Internship participants to the Attendance Model. Interns who do not attend lectures have a higher SRL than apprentices who do not attend lectures.Â Self-Regulated Learning (SRL) merupakan partisipasi aktif individu dalam proses belajarnya (Zimmerman, 1990). Penelitian ini bertujuan untuk menguji perbedaan SRL pada Peserta Magang Kampus Merdeka ditinjau dari faktor lingkungan, diantaranya Sistem Magang (WFO, WFH, dan Hybrid), Durasi Magang (10 jam), dan Model Kehadiran (Mengikuti Perkuliahan dan Tidak Mengikuti Perkuliahan). Hasil penelitian menunjukkan tidak ada perbedaan SRL pada peserta Magang Kampus Merdeka terhadap Sistem Magang dan Durasi Magang. Namun, ada perbedaan SRL pada peserta Magang Kampus Merdeka terhadap Model Kehadiran. Peserta magang yang tidak mengikuti perkuliahan memiliki SRL yang lebih tinggi dibandingkan peserta magang yang tidak mengikuti perkuliahan.